PARSEL (Pemanfaatan Air Rebusan Seledri) Untuk Menurunkan Tekanan Darah Penederita Hipertensi Pada Wanita Menopause - Rabia Wahdah; Cintia N F; Putri Yuliantie; Elysa Marini (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is a highly prevalent health problem among the elderly. Complementary therapy is a disease management method used to support conventional medical treatment or as an alternative treatment option outside of conventional medical treatment. Pharmacological treatments used for hypertension include beta blockers, angiotensin-converting enzyme (ACE) inhibitors, diuretics, alpha blockers, and calcium channel blockers. A consequence of using diuretics is that potassium levels in the body are flushed out alongside sodium in urine. Yhe depletion of potassium can cause muscle cramps and, in extreme cases, death. A health problem identified in Tajau Landung Village, RT 03, within the Sungai Tabuk I Community Health Center (UPTD), is the elderly with hypertension. The purpose of this community service activity, as a non-pharmacological therapy, is to help lower blood pressure in hypertension sufferers, especially menopausal women with hypertension. The methods used in this counseling and demonstration are to increase menopausal women's knowledge of simple non-pharmacological therapies that can be applied at home. The conclusion of the community service activity of celery boiled water to lower blood pressure in hypertension sufferers was carried out through counseling using PowerPoint in the work area of Sungai Tabuk 1 Health Center, Tajau Landung Village, Rt.03.